Impact of ERP systems on process automation and technological performance in the agro-industrial sector of SMEs in Peru. - Dioses Castillo, Roxana Katherine; Llacsahuanga Salazar, Gregoria Yacely; Pingo Lozada, José Félix; Sanchez García, Ingrid Estefani (LACCEI, 2025)
Organizations currently face critical operational challenges due to the lack of automation in internal processes, which affects their efficiency and adaptability. In this context, the implementation of ERP systems is presented as a strategic solution. This study aims to guide Peruvian agro-industrial SMEs towards improving their efficiency and competitiveness in a dynamic environment through the use of ERP systems. A systematic evaluation of 627 articles obtained from a database such as Scopus, Scielo, Redalyc and Ebscohost was carried out, of which 36 studies managed to meet the established inclusion parameters. The findings indicate that ERP systems positively impact process automation and the technological performance of SMEs, optimizing information management, reducing operating costs and strengthening internal interaction through data centralization. However, barriers such as lack of financing and training were identified. In conclusion, ERP systems are essential tools to face the operational and technological challenges of the agro-industrial sector. User training and management support are key factors for successful implementation, highlighting the need to overcome current limitations to maximize benefits and enhance greater competitiveness in the technological age.